A highly stretchable and ultra-sensitive strain sensing fiber based on a porous core–network sheath configuration for wearable human motion detection. Issue 34 (16th August 2022) - Liu, Jun; Wang, Peng; Li, Guoxian; Yang, Li; Yu, Wei; Meng, Chuizhou; Guo, Shijie
Abstract : A flexible and elastic fiber-shaped strain sensor is made using a wet-spinning and dip-coating approach. It adopts a coaxial configuration of a porous core and a conductive sheath, which can be integrated into gloves for hand gesture recognition. Abstract : Functional fibers have attracted much research attention due to their potential application in developing advanced electronic textiles for wearable devices. However, challenges still exist in preparing high-performance fiber-shaped sensors with superior flexibility and stretchability while achieving a high sensitivity and a wide detection range. Herein, we propose the design and fabrication of an ultra-flexible and super-elastic fiber-shaped strain sensor via a facile combining approach of wet-spinning and dip-coating. The sensor adopts a core–sheath configuration of liquid metal droplets dispersed in porous thermoplastic polyurethane as a substrate core and a carbon nanotube intertwined network embedding silver nanowires as a strain sensitive sheath. By taking advantage of both the composition of multiple functional materials and the design of a microstructured device configuration, the developed fiber-shaped sensor exhibits an ultrahigh sensitivity (maximum gauge factor of 7336.1), an extremely large workable strain range (500%), a low strain detection limit (0.5%), a fast response time (200 ms) and good stability (10 000 cycles). In addition, the sensor is temperature insensitive, inert under harsh solution conditions, degradable and recyclable. Intriguingly, the fiber-shaped sensor can be used to detect various human motions and gestures by directly attaching to skins or elaborately weaving into textiles, demonstrating its great potential in human healthcare monitoring and human–machine interactions.